2003
DOI: 10.1161/01.cir.0000106903.98196.b6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B-Type Natriuretic Peptide Levels in Ambulatory Patients With Established Chronic Symptomatic Systolic Heart Failure

Abstract: Background-The diagnostic and prognostic values of plasma B-type natriuretic peptide (BNP) testing are established. However, the range of plasma BNP levels present in the setting of chronic, stable systolic heart failure (HF) is unclear. Methods and Results-We followed up 558 consecutive ambulatory patients with chronic, stable systolic HF (left ventricular ejection fraction Ͻ50%) treated at a specialized outpatient HF clinic between November 2001 and February 2003. Retrospective chart review was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(70 citation statements)
references
References 10 publications
2
61
0
7
Order By: Relevance
“…121 Measurement of BNP or NT-proBNP is useful for establishing prognosis in chronic HF. Elevated BNP or NTproBNP levels parallel HF disease severity, assessment by New York Heart Association (NYHA) class, elevated filling pressures, or worse hemodynamics [121][122][123][124] and are suggestive of worse clinical outcomes and mortality in chronic HF.…”
Section: Natriuretic Peptides: Bnp or Nt-probnpmentioning
confidence: 99%
See 1 more Smart Citation
“…121 Measurement of BNP or NT-proBNP is useful for establishing prognosis in chronic HF. Elevated BNP or NTproBNP levels parallel HF disease severity, assessment by New York Heart Association (NYHA) class, elevated filling pressures, or worse hemodynamics [121][122][123][124] and are suggestive of worse clinical outcomes and mortality in chronic HF.…”
Section: Natriuretic Peptides: Bnp or Nt-probnpmentioning
confidence: 99%
“…121 Measurement of BNP or NT-proBNP is useful for establishing prognosis in chronic HF. Elevated BNP or NTproBNP levels parallel HF disease severity, assessment by New York Heart Association (NYHA) class, elevated filling pressures, or worse hemodynamics [121][122][123][124] and are suggestive of worse clinical outcomes and mortality in chronic HF. [125][126][127][128] Further data demonstrated that each 100-pg/mL increase in BNP was associated with a 35% increase (95% confidence interval [CI], 22-49; P=0.096) in the relative risk of death.…”
Section: Natriuretic Peptides: Bnp or Nt-probnpmentioning
confidence: 99%
“…Elevated MMP‐9 levels may help identify patients at risk before an increase occurs in ventricular pressure overload, which reflects ongoing ventricular remodeling. The value of BNP levels for guiding therapy in addition to clinical symptom‐based treatment seems to be limited,9, 10, 11, 21 despite the undisputed diagnostic and prognostic importance of these values 6, 7, 8. The benefits of predicting HF events may be offset by non‐HF events.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, elevated plasma concentrations of brain natriuretic peptide (BNP) show notable associations with development of left ventricular dysfunction and HF 5. Although elevated BNP concentrations have diagnostic and prognostic importance,6, 7, 8 whether intense therapy for HF guided by BNP values is superior to therapy guided by clinical symptoms is unclear 9, 10, 11. BNP play important roles in maintaining cardiorenal homeostasis under physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Указано, что использование в качестве биомарке-ров МНУП у амбулаторных больных с хронической СН может влиять на клиническую оценку состояния боль-ного, особенно в тех случаях, когда причина развития одышки неясна [4,[20][21][22][23][24][25]. В острой ситуации резуль-таты оценки уровня НУП в качестве биомаркеров имеют более высокую чувствительность по сравнению со специфичностью и могут быть полезнее для исклю-чения СН, а не для ее подтверждения [26].…”
Section: Biomarkers Of Heart Failure биомаркеры сердечной недостаточнunclassified